Analisis Rasio Profitabilitas, Rasio Solvabilitas, Rasio Likuiditas dan Rasio Pasar Terhadap Kinerja Keuangan PT. Bank Central Asia Tbk - Ayi Srie Yuniwati; Anggun Lutfyyah Aulia; Aik Rostika Permata Putri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Financial ratios are technique and indicator for seeing the growth rate of a company's financial performance by comparing the items contained in the financial reports. This research will analyze Liquidity Ratio, Profitability Ratio, Solvency Ratio and Market Ratio. This research was created to analyze PT Bank Central Asia Tbk’s financial performance. Period 2020 to 2022. The research methods used a qualitative research design using a descriptive approach and quantitative secondary data sources. The results are the profitability ratio, the company is able to utilize company assets well and make its own capital efficient to generate profits. At solvency ratio, the company's dominant assets come from debt, which shows a good condition. In the liquidity ratio, the company shows low liquidity, indicating that the company's ability to fulfill its debts to depositors is still not fulfilled. At market ratio, it presents the selected company's profit for each outstanding share. EPS has showed increases and decreases where there has been a fluctuating decrease in 2020 to 2021. According to the PER analysis, it has decreased and only showed an insignificant increase in 2020 -2021. Dividends on the number of outstanding shares that will be distributed to shareholders are getting higher. Meanwhile, PBV is in an overvalued condition which indicates expensive, but the high price could be shows the performance of PT. Bank Central Asia which is in well performance and its shares are liquid.